Financial Literacy As An Effort To Sustain Small And Medium Enterprises In Denpasar - I Made Budiasa; Luh Putu Kirana Pratiwi; Ni Made Kencana Maharani (Journal of Sustainable Development Science, 2022)
Financial literacy is an individual's knowledge of finance and an individual's ability to make effective financial decisions in terms of financial management, selection of funding sources and choosing where to allocate funds for investment. The resilience of Micro, Small and Medium Enterprises to the crisis makes Micro, Small and Medium Enterprises an important asset for the sustainability of a country's economy. This study aims to analyze the level of financial literacy in micro, small and medium enterprises in Denpasar City Micro, Small and Medium Enterprises through five main variables, namely financial knowledge, financial ability, financial behavior, financial attitudes and financial performance. The method used in this research is descriptive quantitative using data obtained from the Denpasar City Cooperative Service. The results showed that the level of financial literacy in the Micro, Small and Medium Enterprises of Denpasar City, Micro, Small and Medium Enterprises of Denpasar City was in medium criteria. A high level of financial literacy will potentially provide a higher productivity value in business sustainability.